Charles Maurras – osobnost a l´Action française - Aleš Vrbata (Theatrum Historiae)
The author in his article introduces into life, political ideas and ideology of Charles Maurras as a person and as a head of l‘Action française. He is considered to be one of those who helped to prepare ideological basis of the french fascism of 30‘s and 40‘s. The autor explains origins of his thinking showing his childhood and background in the french province of Provence where Maurras himself experienced the french tradicionalism, monarchical upbringing and where his studies of literature, philosophy, history and other subjects helped him to define the first of his attitudes. Later on, in Paris, his attitudes will get clearer and will get monarchical and integralist aspect. Maurras collaborates with Félibrige de Paris, with tradicionalist press, publishes his first books and specifies his definition of french culture and civilization which is connected with his criticism of the french revolutionary tradition. In the end of 19th century enters l‘Action française which was originally republican movement. Maurras makes it monarchical. The movement participated in Drefyfus affair and as highly nationalistic called for revenge against Germany. The author explains the importance of connection which existed between l‘Action française, Maurras and the catholic church – ideologically and politically – and the importance of break up that occured in 1926 and which caused number of problems both for l‘Action française as movement and ideological current and weakened its force on the french political scene. The author mentions also importance of other members of Action française as for example Léon Daudet, Jacques Bainville and others, activity of this movement during Vichy regime and attempts to restore this movement (or journal of Action française) after the Second world war.